Efficacy of Probiotics to Control Ammonia in Oreochromis Niloticus Fishponds in Volta Region, Ghana - Murali, N.; Nair, S.G.; Ibañez-Arancibia, E.; De los Rios, P.; Kalidass, S.; Муралі, Н.; Наїр, С.Г.; Ібанес-Аранчібія, Е.; Де лос Ріос, П.; Калідасс, С. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Current intensification of aquaculture where the organic loads with toxic compounds like NH3 and H2S shoot up beyond the level where naturally occurring bacteria cannot decompose the wastes has necessitated the use of probiotics. Objective. The objective was to use five different probiotics to treat ammonia and analyze the effects on water quality and changes in it in fishponds. Methods. Five different probiotic compositions were used, and the water quality was measured, mainly for ammonia concentration. Results. 5 different ponds located in the village of Agortha, Volta Region, Ghana, were treated with 5 different products simultaneously for 3 months. The concentration of ammonia has come to zero in 2 ponds with pH equal to 8. Conclusions. The results revealed that probiotics addition was efficient in decreasing the ammonia concentration in fishponds.